PENGARUH QUALITY OF WORK LIFE (QWL) DAN KEPERCAYAAN PADA PIMPINAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) MELALUI KOMITMEN ORGANISASIONAL (STUDI PADA BALAI LATIHAN KERJA PEMERINTAH SEPULAU LOMBOK) - Fitrijayanti, Diana (Jurnal Magister Manajemen, 2015)
This study aims to reveal the influence of Quality of work life and trust in leaders on the organizational commitment; and to examine the influence of trust in leaders and organizational co0mmitment on organizational citizenship behavior. This study was conducted at the goverment-owned training centres throughout Lombok island. This is an associative causal relationship study involving 86 employees of the centres as respondents of the study. For data analysis, the researcher employed Path Analysis Research Design of SPSS Amos program. Result of the study show that the Quality of work life positively and significantly influenced the organizational commitment. Also trust in leaders influenced the organizational commitment. Quality of work life positively and significantly influenced the organizational citizenship behavior. However, the trust in leaders negatively and insignificantly influenced the organizational citizenship behavior. Finaly, it was found that organizational commitment positively but not significantly influenced the organizational citizenship behavior of the employees of the goverment-owned training centres throughout Lombok island. Keywords: organizational citizenship behavior, Quality of work life, trust in leaders, organizational commitment.